Law Enforcement For Clothes Smuggling Formallyillegal - Ridwan Lubis, Muhammad (Universitas Islam Sumatera Utara, 2023)
The crime of smuggling is very common in Indonesia, it's just that in imposing criminal sanctions, its implementation only focuses on imprisonment, because the concept of